An Analytical Approach for Analysis of Slider Bearings with Non-Newtonian Lubricants. (15th January 2014) - Chu, Li-Ming; Hsu, Hsiang-Chen; Chen, Jiann-Lin
Abstract : In this study, a regular perturbation technique is utilized to derive the modified Reynolds equation which is applicable to power-law lubricant. The performance of slider bearings including pressure distributions, velocity distributions, film thickness, load capacity, flow rate, shear force, and friction coefficient is also derived analytically for various ξ, flow indices (n ), and outlet film thicknesses (H 0 ). These analytical solutions are clear to find the effects of the operation parameters rather than numerical methods. It can be simply and fast used for engineers. Subsequently, these proposed analytical solutions are used to analyze the lubrication performance of slider bearing with the power-law fluids.